NifH-Harboring Bacterial Community Composition across an Alaskan Permafrost Thaw Gradient - Penton, C. Ryan; Yang, Caiyun; Wu, Liyou; Wang, Qiong; Zhang, Jin; Liu, Feifei; Qin, Yujia; Deng, Ye; Hemme, Christopher L.; Zheng, Tianling; Schuur, Edward A. G.; Tiedje, James; et al. (Frontiers in Microbiology, 2016)
Since nitrogen (N) is often limiting in permafrost soils, we investigated the N2-fixing genetic potential and the inferred taxa harboring those genes by sequencing nifH gene fragments in samples taken along a permafrost thaw gradient in an Alaskan boreal soil. Samples from minimally, moderately and extensively thawed sites were taken to a depth of 79 cm to encompass zones above and below the depth of the water table. NifH reads were translated with frameshift correction and 112,476 sequences were clustered at 5% amino acid dissimilarity resulting in 1,631 OTUs. Sample depth in relation to water table depth was correlated to differences in the NifH sequence classes. NifH sequences most closely related to group I nifH-harboring Alpha- and Beta Proteobacteria were in higher abundance above water table depth while those related to group III nifH-harboring Delta and Gamma Proteobacteria were more abundant below. The most dominant below water table depth NifH sequences, comprising 1/3 of the total, were distantly related to Verrucomicrobia-Opitutaceae. Overall, these results suggest that permafrost thaw alters the class-level composition of N2-fixing communities in the thawed soil layers and that this distinction corresponds to the depth of the water table. These nifH data were also compared to nifH sequences obtained from a study at an Alaskan taiga site, and to those of other geographically distant, non-permafrost sites. The two Alaska sites were differentiated largely by changes in relative abundances of the same OTUs, whereas the non-Alaska sites were differentiated by the lack of many Alaskan OTUs, and the presence of unique halophilic, sulfate- and iron-reducing taxa in the Alaska sites.